Peran Relawan Pajak terhadap Tingkat Kepatuhan Wajib Pajak Pribadi (Pph Pasal 21) yang Terdaftar di KPP Pratama Jember - Bagus Alif Nugieanto; Diyah Probowolan; Achmad Syahfrudin (CV. Ulil Albab Corp, 2023)
The role of tax volunteers on the compliance of private taxpayers registered at KPP Pratama Jember. This study aims to examine the effect of knowledge, skills, and responsibilities of tax volunteers on taxpayer compliance. This type of research is quantitative. The data used in this study are primary and secondary data. The sample used as the object of this research is 100 respondents who use the Non-Probability Sampling method. The research method used in this research consists of validity test, reliability test, multiple linear regression analysis, classical assumption test, hypothesis test, and coefficient of determination test. The results of the study state that knowledge has a significant effect on the level of taxpayer compliance. The results show that skills have a significant effect on the level taxpayer compliance. The results state that responsibility has a significant effect on the level taxpayer compliance.